Notes about Configuration of Organizational Justice and Social Capital: Impact on Satisfaction and Commitment - Wahyu Abdillah Utomo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study is a review of Heru Kurnianto Tjahjono's article, Olivia Fach runnisa, Majang Palupina, Majang runnisa, in the International Journal of Business Excellence journal, Vol.17,No.3, 2019 with the title Configuration of organizational justice and social capital: their impact on satisfaction and commitment. This study argues that the limited information of individuals in responding to organizational policies forces them to judge fairness subjectively. Referring to social identity theory, this study proposes social capital as a key factor in explaining individual behavior in evaluating distributive justice and procedural justice. Individuals with high social capital tend to be group-oriented with different principles of justice. Using an experimental design, this study addresses the controversy over the impact of distributive and procedural justice on job satisfaction and organizational commitment. Substantial findings in this study explain that contextual aspects, such as distributive justice, procedural justice, and social capital, play a major role in elaborating organizational satisfaction and commitment.